Transakcje sprzedaży chłopów w powiecie mohylowskim w pierwszej dekadzie XIX wieku - Skrabacz-Nejman, Ewelina (Przegląd Wschodnioeuropejski, 2024)
Nowadays, peasants are becoming the subject of scientific studies more and more often. The problem of selling the peasants became an important part of current historical research on rural population. This issue takes an important part within the scope of social history but also history of economics. The aim of the research was to describe phenomenon of selling the peasants in microscale of Mohylów Podolski poviat within Podillia Province of Russian Empire during the first decade of 19th century. At that time Podillia was already an integral part of Russian Empire however it was still under strong social and cultural influence of recently fallen Polish-Lithuanian Commonwealth. A source query in the court books of the Civil Chamber of the Land Court of the Mohylów Podolski poviat revealed 24 commercial entries regarding the sale of serfs. Transactions were expressed in both Polish zlotys and rubles. There is a great deal of variation in transaction values; from 29 to 100 rubles (from 200 to 700 zlotys) for male souls, from 13 to 30 rubles (from 90 to 210 zlotys) for a female soul and from 46.5 to 47.5 rubles (from 325.5 to 333 zlotys) for whole family. The differentiation of transaction values in individual categories could result from the age, health and qualifications of a peasant. The main reasons for the sale were: immediate financial need, repayment of previous credit obligations or compensation in the event of the marriage of the subjects and the related departure to another owner.